In search of a growth model for Italy: The failed attempt of an export-led recovery strategy? - Alessandro Bramucci (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
We analyse Italy's growth pattern from 2001 to 2019 using the demand and growth regime categories proposed in the post-Keynesian tradition and recently adopted in the comparative political economy (CPE) literature. We argue that Italy followed an export-led recovery strategy after the Global Financial Crisis. In this respect, Germany's growth model emerged as the successful one to follow. In the dominant view, Germany's economic success since the mid-2000s was attributed to a series of painful but necessary economic reforms. The success of Germany's export-led mercantilist regime became particularly attractive to Italy given the similar export-oriented manufacturing industry. However, Italy has followed the "wrong" German model based on wage compression and restrictive budget policies while the "true" German model is based on non-price competitiveness factors. To conclude, we show the contradictions of the mercantilist export-led regime.
Keywords: E10; E69; F14; 330; Demand and growth regimes; export-led growth; competitiveness; internal devaluation; Germany; Italy